Elevated insulin-like growth factor 2 mRNA binding protein 1 levels predict a poor prognosis in patients with breast carcinoma using an integrated multi-omics data analysis - Li, Shiqi; Jiang, Meixiu (Frontiers in Genetics, 2022)
Background: Insulin-like growth factor 2 mRNA binding protein 1 (IGF2BP1) controls the cytoplasmic fate of certain mRNAs and is hypothesized to predict a poor patient prognosis in several malignant tumors. However, the prognostic relevance of IGF2BP1 in breast cancer remains debatable. Methods: We interrogated large publicly available datasets from the Gene Expression Omnibus (GEO), The Cancer Genome Atlas (TCGA), and cBioportal databases to analyze the genetic alterations in the expression levels of IGF2BP1 in patients with invasive breast carcinoma (BRCA), and to discern the prognostic value of IGF2BP1 in BRCA. We applied Gene Ontology (GO), the Kyoto Encyclopedia of Genes and Genome (KEGG), and gene set enrichment analysis (GSEA) to uncover a functional association between IGF2BP1 and BRCA using differentially expressed genes (DEGs), and we screened genes and proteins related to BRCA. Results: We determined that both genetic alterations in IGF2BP1 (approximately 10%) and an increase in IGF2BP1 mRNA levels were related to certain cancer subtypes and an unfavorable prognosis in BRCA patients, and we then established an OS nomogram upon our multivariate regression model. The DEGs and IGF2BP1-correlated genes/proteins that we noted implied the involvement of cornification, keratinization, drug/xenobiotic metabolism by cytochrome P450, chemical carcinogenesis, cell interactions, and cell adhesion to the extracellular matrix (ECM) pathways with respect to the prognostic relevance of IGF2BP1. Conclusion: In summary, our results indicated that both genetic alterations in IGF2BP1 and increased levels of IGF2BP1 mRNA and protein predict a poor patient prognosis in BRCA patients.